2013
DOI: 10.2478/s13380-013-0131-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic metacognition as a link between brain and behavior in schizophrenia

Abstract: Deficits in metacognitive capacity in schizophrenia can be conceptualized as existing along a spectrum from more discrete to more synthetic activities. These capacities may be of great importance in schizophrenia research given their potential to mediate and moderate the impact of illness-related factors on outcome. To explore this possibility this review summarizes research on synthetic metacognition using a paradigm in which metacognitive capacity is rated on the basis of spontaneously produced personal narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 66 publications
1
31
0
2
Order By: Relevance
“…One way to conceptualise this larger interruption of self as it is manifest in the lives of people with schizophrenia is that the elements of subjective experience described here: fragmentation, an ever-changing interpersonal field and a loss of agency may all be linked to a partial collapse in processes that several authors have referred to as synthetic metacognition 26. Metacognition has been conceptualised as a spectrum of activities ranging from discrete to more synthetic activities.…”
Section: Schizophrenia and The Interruption Of Beingmentioning
confidence: 99%
“…One way to conceptualise this larger interruption of self as it is manifest in the lives of people with schizophrenia is that the elements of subjective experience described here: fragmentation, an ever-changing interpersonal field and a loss of agency may all be linked to a partial collapse in processes that several authors have referred to as synthetic metacognition 26. Metacognition has been conceptualised as a spectrum of activities ranging from discrete to more synthetic activities.…”
Section: Schizophrenia and The Interruption Of Beingmentioning
confidence: 99%
“…Metacognition in this sense refers to a spectrum of mental activities that involves reflective capacities which range from discrete acts in which people recognize specific thoughts and feelings to more synthetic acts in which an array of intentions, thoughts, feelings, and connections between events are integrated into larger complex representations (Lysaker et al 2013;Semerari et al 2003). Synthetic forms of metacognition can be distinguished from more traditional elements of social cognition in that they occur within intersubjective discourse between people and are related to the extent to which pieces of information are coherently integrated rather than whether or not specific judgments are accurate.…”
Section: Introductionmentioning
confidence: 99%
“…This was the same for self-reflectivity, understanding of others, decentration, and mastery separately, which is in contrast to Lysaker, Shea et al (2010), who found that the variance in mastery was significantly predicted by cognitive functioning. Lysaker et al (2005), Lysaker, Bob et al (2013), andMacBeth et al (2013) found that poor metacognition leads to social functioning deficits in schizophrenia and that metacognitive training results in better social functioning. The variability in time since onset of the disorder may influence this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Metacognitive capacities "allow persons to form a detailed picture of their own mental states, of the wishes and intentions of the others, and of the inner and social cues that trigger psychological pain", according to Lysaker, Erickson et al (2011, p. 413), "and thereby to cope with challenges and solve complex social problems". The concept is thus strongly related to the ability to cope with the challenges of everyday life, meaning that impaired metacognitive abilities can have far-reaching consequences (Lysaker, Bob et al, 2013).…”
mentioning
confidence: 99%